1998
DOI: 10.1097/00007890-199812270-00013
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Autoimmune Hepatitis After Liver Transplantation1

Abstract: Recurrence of autoimmune hepatitis in the graft is a common event with an incidence that increases over time as immunosuppression is reduced. Although response to treatment is poor, patient and graft survival do not appear to be decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
147
2
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(154 citation statements)
references
References 21 publications
3
147
2
2
Order By: Relevance
“…Criteria used to distinguish rejection from AIH can be melded into generalized criteria applicable to other causes of late liver allograft dysfunction, [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] including: (1) histopathological evidence of liver injury showing a pattern compatible with the diagnosis (liver tests are usually elevated in a pattern consistent with the diagnosis); (2) positive serological, molecular biological, immunological, or radiographic evidence of pathogen or possible cause of injury; and (3) other causes of similar histopathological changes and elevated liver tests, if present, have been reasonably excluded. Table 1 shows approximate incidences, risk factors, and clinical, immunological, and radiological observations for common causes of late dysfunction.…”
Section: Generalized Criteriamentioning
confidence: 99%
“…Criteria used to distinguish rejection from AIH can be melded into generalized criteria applicable to other causes of late liver allograft dysfunction, [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] including: (1) histopathological evidence of liver injury showing a pattern compatible with the diagnosis (liver tests are usually elevated in a pattern consistent with the diagnosis); (2) positive serological, molecular biological, immunological, or radiographic evidence of pathogen or possible cause of injury; and (3) other causes of similar histopathological changes and elevated liver tests, if present, have been reasonably excluded. Table 1 shows approximate incidences, risk factors, and clinical, immunological, and radiological observations for common causes of late dysfunction.…”
Section: Generalized Criteriamentioning
confidence: 99%
“…5,9,11,16 Our experience was too small to establish these associations. Similarly, we were unable to show that the principal program of immunosuppression (tacrolimus or cyclosporine) was an important determinant of recurrence.…”
Section: Discussionmentioning
confidence: 88%
“…3,4 Furthermore, autoantibodies and hypergammaglobulinemia disappear in most patients within 2 years. 1,2 Despite these successes, recurrent disease is possible, 2,3,[5][6][7][8][9][10][11][12][13] and recent reports have indicated that it may lead to cirrhosis and graft failure. 2,8,12 Furthermore, the immunoreactive propensity of the recipient may contribute to greater frequencies of acute rejection, steroid-resistant rejection, and chronic rejection, especially if corticosteroids are withdrawn in the posttransplantation period.…”
mentioning
confidence: 99%
See 2 more Smart Citations